Anisotropic and omnidirectional focusing in Luneburg lens structure with gradient photonic crystals. (6th December 2016) - Zhao, Yuan-Yuan; Zhang, Yong-Liang; Zheng, Mei-Ling; Dong, Xian-Zi; Duan, Xuan-Ming; Zhao, Zhen-Sheng
Abstract: We propose a flexible design for implementation of the Luneburg lens with gradient photonic crystals. The full-wave simulation results demonstrate the excellent performance of omnidirectional focusing of the designed Luneburg lens over a broad frequency band, and firstly exhibit anisotropic focusing in the designed Luneburg lens with a specific frequency band. In this study, our effort is focused on figuring out the operating wavelength range where the effective medium approximation theory is applicable, and the mechanism for generating anisotropic and omnidirectional focusing in Luneburg lens structure.